Systematics and Ethnobiology of Spineless Leaf Common Pandanus (Pandanus tectorius Parkinson Ex Du Roi; Pandanaceae) from Kelapan Island, Bangka and Belitung, Indonesia - Sela Agustika; Santiago Santiago; Eddy Nurtjahya; Ary Prihardhyanto Keim; Nissa Arifa; Muhamad Nikmatullah; Ida Farida Hasanah; Wawan Sujarwo (Journal of Tropical Ethnobiology, 2020)
Pandanus tectorius Parkinson ex Du Roi forma integrifolius S. Agustika, S. Santiago and A.P. Keim is a new forma described from Kelapan Island in the Bangka and Belitung Province, Indonesia. This new forma is identified through the distinctive morphological character of spineless leaf margin. These facts are important to be explained related to the unique morphological phenomenon recently discovered in a small population of P. tectorius found in one of the small islands around Bangka Island. The result showed that the phenomenon of spineless leaves in P. tectorius found in Kelapan Island is related with the absence of predator, especially frugivore that consume the fruit of the species. In other words, the complete absence of bats in Kelapan Island apparently triggers the individuals of P. tectorius in the island to stop developing the spines in the leaf margin in order to protect the fruits from predators. The people of Kelapan Island harvest the leaves of P. tectorius for making mats.